NK cells from Men Who Have Sex with Men at high risk for HIV-1 infection exhibit higher effector capacity (2023)
ABSTRACT: Despite being under constant exposure to HIV-1, some individuals do not show serological or clinical evidence of infection and are known as HESN (HIV-Exposed Seronegative). Multiple studies in different HESN cohorts have linked the NK cells as a correlate of resistance; however, little is known about the role of these cells in Men Who Have Sex with Men (MSM) with high risk sexual behaviors. We evaluated a general overview of activation and effector features of NK cells of MSM co-cultured with LT CD4+ HIV+ in which MSM at high risk of HIV-1 infection (HR-MSM) exhibit higher capacity to eliminate infected cells, reduced percentages of CD69+ cells when compared to MSM at low risk of infection (LR-MSM). In addition, we found that, despite the lower levels of CD69+ NK cells on HR-MSM group, within this population, higher percentages of CD69+ IFN-γ+ and CD69+ NKG2D+ NK cells were found together with higher levels of RANTES and Granzyme B production with higher antiviral capacity, resulting in a lower concentration of p24 protein and p24+ CD4+ T cells. Altogether, this information suggests that NK cells of MSM could impact the capacity to face the viral infection.